Positive emotion modulates cognitive control: An event‐related potentials study. Issue 2 (8th February 2013) - Xue, Song; Cui, Jingjing; Wang, Kangcheng; Zhang, Songyan; Qiu, Jiang; Luo, Yuejia
<x xml:space="preserve">Abstract</x> There is substantial evidence to indicate that negative emotion can modulate cognitive control processing. However, only a few studies have investigated this effect with positive emotion. Therefore, the present study explored the electrophysiological correlates of the impact of positive emotional stimuli on cognitive control, using event‐related potentials (ERPs). Sixteen healthy young adults completed a modified Simon task (Simon, 1969). Behavioral data indicated that reaction times were faster for positive emotional stimuli than for neutral emotional stimuli in the incongruent condition, but not in the congruent condition, which suggested that positive emotion expedited conflict resolution. The ERP data showed that two negative ERP components (N300–400 and N450–550) were associated with the positive emotional stimuli in the incongruent minus congruent condition. It is suggested that these components may respectively be related to the conflict monitoring (N300–400) and response selection (N450–550) stages of cognitive control processing. Overall, our results indicated that positive emotion could facilitate cognitive control processing. These results are in line with the neuropsychological theory, according to which, positive emotion could modulate cognitive control mediated by increased dopamine levels in frontal brain areas.